The quality of life of postmenopausal women with hip and knee advanced dysfunction due to osteoarthritis prior to joint replacement - Morawik, Iwona; Jurewicz, Alina; Jędrych, Marian; Jabłoński, Mirosław (Polish Journal of Public Health, 2012)
Introduction. Surgical replacement of hip and knee joints with advanced degenerative and deformative changes is a method commonly used for treatment of such important and frequent ailments of the locomotor organ. In accordance with an obligatory system of scheduling in Poland the waiting time for a hip or knee endoprothesoplasty takes up to two years.Aim. The aim of the research was to characterize and assess the quality of life of postmenopausal patients with the degenerative changes of hip joints (coxsarthrosis) and knee joints (gonarthrosis) waiting for joint arthroplasty.Material and methods. The research was based on two groups of postmenopausal women aged 50-62 with advanced osteoarthritis of the hip (n=59) and knee (n=51). The quality of life just prior to the planned surgery was measured by means of an individually prepared survey where two questions from the HRQ Johansson and co. survey (1992) were used. In the statistical analysis with the significance of p